In vitro and in vivo performance of methacrylated gellan gum hydrogel formulations for cartilage repair - Vilela, Carlos A. (2018)
Methacrylated gellan gum (GGMA) formulation is proposed as a second-generation hydrogel for controlled delivery of cartilage-forming cells into focal chondral lesions, allowing immediate in situ retention of cells and 3D filling of lesion volume, such approach deemed compatible with an arthroscopic procedure. Formulation optimization was carried out in vitro using chondrocytes and adipose mesenchymal stromal/stem cells (ASCs). A proof-of-concept in vivo study was conducted using a rabbit model with induced chondral lesions. Outcomes were compared with microfracture or non-treated control. Three grading scores were used to evaluate tissue repair after 8 weeks by macroscopic, histological and immunohistochemical analysis. Intense collagen type II and low collagen type I gene and protein expression were achieved in vitro by the ASC + GGMA formulation, in light with development of healthy chondral tissue. In vivo, this formulation promoted significantly superior de novo cartilage formation compared with the non-treated group. Maintenance of chondral height and integration with native tissue was further accomplished. The physicochemical properties of the proposed GGMA hydrogel exhibited highly favorable characteristics and biological performance both in vitro and in vivo, positioning itself as an attractive xeno-free biomaterial to be used with chondrogenic cells for a cost-effective treatment of focal chondral lesions. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1987-1996, 2018.